2023
DOI: 10.1186/s12936-023-04630-2
|View full text |Cite
|
Sign up to set email alerts
|

An active and targeted survey reveals asymptomatic malaria infections among high-risk populations in Mondulkiri, Cambodia

Abstract: Background Malaria is a mosquito-borne disease that is one of the most serious public health issues globally and a leading cause of mortality in many developing countries worldwide. Knowing the prevalence of both symptomatic and asymptomatic malaria on a subnational scale allows for the estimation of the burden of parasitaemia present in the transmission system, enabling targeting and tailoring of resources towards greater impact and better use of available capacity. This study aimed to determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…A cross-sectional study in Cambodia revealed that females have a lower risk of contracting malaria than males (aOR = 0.61; 95% CI: 0.38–0.97, p = 0.04) [ 16 ]. Nonetheless, a study conducted in Kalimantan indicated no significant links between gender and malaria infection [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A cross-sectional study in Cambodia revealed that females have a lower risk of contracting malaria than males (aOR = 0.61; 95% CI: 0.38–0.97, p = 0.04) [ 16 ]. Nonetheless, a study conducted in Kalimantan indicated no significant links between gender and malaria infection [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The report also revealed that individuals under 25 years old were more likely to be infected with malaria than their older counterparts (aOR = 2.526; 95% CI: 0.804–7939) [ 17 ]. Another study documented no remarkable association between age and malaria infection [ 16 ]. Ethnicity was also not a considerable factor in contracting malaria [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations